Emotional Responses and Comprehension in Asynchronous Communication: A Literature Review of Changing Digital Interaction Patterns - Azmi Nawaf; Darul Naad; Muhammad Azwar; Lahmuddin Lubis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The advancement of digital technology has shifted human communication patterns from synchronous to asynchronous modes. This study aims to describe the characteristics of asynchronous communication, analyze its impact on message comprehension, and explain how it influences users’ emotional responses. Using a qualitative descriptive approach based on a literature study, this research reviews relevant works in digital communication, cognitive psychology, and emotional response theories. Findings indicate that asynchronous communication offers advantages in time flexibility and message processing, but also presents challenges such as limited emotional cues and potential misunderstandings. Message comprehension is closely tied to an individual’s cognitive capacity, while emotional responses are more filtered yet susceptible to emotional detachment. This study contributes theoretically by linking cognitive and affective aspects in digital communication and offers practical insights for developing more empathetic communication strategies in the digital era.